The Mediating Role of Teacher Autonomy in the Relationship between School Climate and Individual Innovativeness - Tuncay Yavuz Ozdemir; Neslihan Cakalci (International Journal of Evaluation and Research in Education (IJERE), 2022)
In this study, the mediation role of teacher autonomy in the relationship between school climate and individual innovativeness was examined based on primary school teachers’ perceptions. The study was conducted with the participation of 603 teachers (239 females and 378 male). For data collection, three different scales were administered to the participants: the school climate scale, the teacher autonomy scale, and the individual innovativeness scale. Regression and correlation analyses were performed to test hypothesis.  Also, Bootstrap analysis was carried out by using IBM SPSS 24.0 (Hayes, 2013) with PROCESS Macro 3 with "Simple Mediation Model 4" to examine the significance of the mediation effect. The results revealed a positive, moderate and significant relationship among school climate, individual innovativeness, and teacher autonomy. According to the results of the Bootstrap analysis, teacher autonomy has a significant mediating effect in the relationship between school climate and individual innovativeness. Finally, in order to measure the significance of the mediating variable’s effect amount, the Sobel test was performed. The obtained Z value was at the desired level, which proves the significant mediating effect of teacher autonomy.